Global inequality - McGill, Kenneth (University of Toronto Press, 2016)
"Inequality is currently gaining considerable attention in academic, policy, and media circles. From Thomas Piketty to Robert Putnam, there is no shortage of economic, sociological, or political analyses. But what does anthropology, with its focus on the qualitative character of relationships between people, have to offer? Drawing on current scholarship and illustrative ethnographic case studies, McGill argues that anthropology is particularly well suited to interrogating global inequality, not just within nations, but across nations as well. The book is designed to be used flexibly in a variety of undergraduate classes--from introductory cultural anthropology, to courses on globalization, economic and political anthropology, and inequality. Brief, accessibly written, and peppered with vivid ethnographic examples that bring contemporary research to life, Global Inequality is a unique offering for undergraduate anthropology courses."--
Keywords: Case studies; Equality; Ethnology; dept.ant; faculty_collection